2013
DOI: 10.1155/2013/267360
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Antioxidant Capacity of Red Wine from Different Production Years and Sources under Censoring

Abstract: The health benefit of drinking wine, expressed as capacity to defend the human organism from the free radicals action and thus reducing the oxidative stress, has already been demonstrated, and the results had been published in scientific literature. The aim of our study was to develop and assess a model able to estimate the antioxidant capacity (AC) of several samples of Romanian wines and to evaluate the AC dependency on the vintage (defined as the year in which wine was produced) and grape variety under pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Progressive censoring has the property of allowing the removal of units at some time points that may not be the final termination point. Referring to Yadav et al [3], Jäntschi et al [4], Chen and Gui [5], Balakrishnan and Aggarwala [6] and Aggarwala [7], we can see more inferences about the progressive censored data. For progressive type II censored data, Lee et al [8] constructed a testing procedure for the lifetime performance index.…”
Section: Introductionmentioning
confidence: 84%
“…Progressive censoring has the property of allowing the removal of units at some time points that may not be the final termination point. Referring to Yadav et al [3], Jäntschi et al [4], Chen and Gui [5], Balakrishnan and Aggarwala [6] and Aggarwala [7], we can see more inferences about the progressive censored data. For progressive type II censored data, Lee et al [8] constructed a testing procedure for the lifetime performance index.…”
Section: Introductionmentioning
confidence: 84%
“…Recent studies have showed that grapes varieties have an impact in the antioxidant activity and bioactive compounds in red wines in different countries as France, Italy, Spain, and Brazil (Mulero;Zafrilla;Cayuela;Martínez-Cachá;Pardo, 2011;Jäntschi;Sestraş;Bolboacă, 2013;Padilha;Telles;Corrêa;dos Santos-Lima;Elias-Pereira, 2017). In Mexico, red wine production is a traditional practice based in Vitis vinifera L. grapes and the variation of their physicochemical and biochemical properties is of great interest for the oenological industry of Baja California.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidative systems include enzymes and nonenzymatic substrates, such as glutathione, coenzyme Q, vitamins C, A, and E, flavonoids, carotenoids, teine from tea [46], and others. Antioxidants are usually found in fruits, vegetables, rice, wine [7], meat, eggs, and other vegetal or animal products, or in food supplements [8].…”
Section: Introductionmentioning
confidence: 99%